Localização de T-KIBS no Brasil: um estudo das aglomerações e seus fatores condicionantes - Guimarães, José Geraldo de Araújo (2009)
This master s degree dissertation was aimed at the study of Knowledge Intensive Business Services (KIBS) in Brazil, in particular, Technology KIBS (T-KIBS) and the identification of the concentration of these activities and its factors. By means of identifying CNAE groups of activities categorized as T-KIBS according to the international literature and with the application of SGT software made available by the Department of Labor in its dissemination of labor statistics program based on the annual relations of social information of year 2006 it was identified the presence of each group of activity in each one of the 5653 Brazilian counties. In the process of identifying these concentration of activities the localization quotients (QL) where calculated for each county and by means of a geo-referencing software individual maps and a consolidated map of all concentration of activities associated with T-KIBS in Brazil was presented. As expected, it was observed a high degree of difference in the level of geographic concentration of activities associated with these services which confirmed the differences referenced in theory as it relates to the type of market and the nature of the production process of these activities. The spectrum of activities is wide, including a range from producers to proliferation of knowledge and this wide spectrum influences the dynamics of location and concentration of activities patterns. Regarding the variables used, the calculation of QL s with reference to number of locations did not explicitly reveal the existence of concentration of activities in comparison to the quantity of employees. In addition to the results originated from the secondary data analysis the intent of this dissertation was to identify the conditional factors for these T-KIBS concentration of activities according to the executives of these companies. Three interviews with executives from companies considered T-KIBS businesses were conducted in cities where the concentration of activities was high and considered in any way to have influenced the process of defining the location of these companies and included conditional factors of these locations. Several important points regarding the location of T-KIBS companies and the dynamics that lead to concentration of activities where identified in interviews. Some of these important points include differences between producers and developers of knowledge and implementation or dissemination of knowledge. While for the earlier the proximity of universities demonstrates to be one of the most relevant factors, for the later, this is not a significant factor due to the high degree of mobility of the work force.